Segregating bodily isomerism or heterotaxy: potential echocardiographic correlations of morphological findings. (3rd April 2017) - Tremblay, Cornelia; Loomba, Rohit S.; Frommelt, Peter C.; Perrin, Donald; Spicer, Diane E.; Backer, Carl; Anderson, Robert H.
Abstract: Background: Bodily isomerism, also referred to as heterotaxy, involves predominantly the thoracic organs, although other organs are usually abnormally positioned. Previously assessed on the basis of splenic anatomy, it is now understood that isomerism is better segregated on the basis of atrial appendage morphology. This allows for anticipation of associated findings. We aimed to assess the accuracy of segregation based on the morphology of the atrial appendages and other structures more easily identified by echocardiography. Methods: We reviewed postmortem specimens of hearts from the archives at four institutions categorised as obtained from patients with "heterotaxy". The cardiac structures were analysed using sequential segmental analysis. Non-cardiac structures were also examined if available. Statistical analyses were performed to compare differences in the settings of right as opposed to left isomerism. Results: Specimens were available from 188 patients. Of these, 57 had left isomerism, and 131 had right isomerism. Atrial appendages were isomeric in all patients. A coronary sinus was found only in left isomerism, whereas a terminal crest, or a Eustachian valve, was found only in right isomerism. Interruption of the inferior caval vein was associated with left isomerism, whereas totally anomalous pulmonary venous connection was associated with right isomerism. Conclusion: Isomerism is uniformly segregated on the basis of the morphology of the atrial appendages, itself defined by the extent of the pectinate muscles. Other features such as the presence of a coronary sinus and systemic venous return can further help with such segregation of isomerism.